2015
DOI: 10.1556/018.66.2015.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative effects of α-lipoic acid in the brain, liver and kidneys in selected mouse organs exposed to zymosan

Abstract: This study investigated the role of exogenous α-lipoic acid (ALA) in the inflammation caused by zymosan application. Seventy-two adult male white mice were divided into twelve groups: three control groups, three Zymosan groups, three ALA groups and three groups being the combination of Zymosan and ALA. In the experimental groups, the animals were decapitated after 3, 6 and 24 hours after the injection. The activity of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…19 In recent studies of sepsis and organ damage models, ALA application was reported to ameliorate the damage in liver and kidney by decreasing inflammatory parameters 7 and by increasing antioxidant levels. 20 Our results are in accordance with previous studies which examined the anti-inflammatory and antioxidant effects of ALA, however, in our study antioxidant GSH levels were not increased via ALA application. Besides, our research aimed F I G U R E 4 (A) Luminol and (B) lucigenin-enhanced chemiluminescence levels in colon tissue of control or colitis-induced rats, which were either sedentary or performed aerobic or resistance exercise for 5 weeks before colitis induction, which were either vehicle or α-lipoic acid (ALA)-treated and which were exposed to second hand smoke or not.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…19 In recent studies of sepsis and organ damage models, ALA application was reported to ameliorate the damage in liver and kidney by decreasing inflammatory parameters 7 and by increasing antioxidant levels. 20 Our results are in accordance with previous studies which examined the anti-inflammatory and antioxidant effects of ALA, however, in our study antioxidant GSH levels were not increased via ALA application. Besides, our research aimed F I G U R E 4 (A) Luminol and (B) lucigenin-enhanced chemiluminescence levels in colon tissue of control or colitis-induced rats, which were either sedentary or performed aerobic or resistance exercise for 5 weeks before colitis induction, which were either vehicle or α-lipoic acid (ALA)-treated and which were exposed to second hand smoke or not.…”
Section: Discussionsupporting
confidence: 93%
“…While there is little research indicating the effect of ALA on colitis, it was shown to be effective on Helicobacter pylori ‐induced gastritis . In recent studies of sepsis and organ damage models, ALA application was reported to ameliorate the damage in liver and kidney by decreasing inflammatory parameters and by increasing antioxidant levels . Our results are in accordance with previous studies which examined the anti‐inflammatory and antioxidant effects of ALA, however, in our study antioxidant GSH levels were not increased via ALA application.…”
Section: Discussionsupporting
confidence: 91%
“…LPS increases hepatic TBARS levels and decreases SOD activity in rats[ 4 ]. In mice, IP injection of zymosan also decreases hepatic SOD activity[ 12 ]. Moreover, in mice LPS combined with D-GalN (1 and 300 mg/kg) increased TBARS levels and decreased SOD activity[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Cuzzocrea et al[ 11 ] demonstrated that zymosan did not induce severe liver injury in inducible NO synthase (iNOS)-deficient mice compared to that in wild-type mice. Additionally, oxidative stress may mediate PAMP-induced organ injury, because lipid peroxidation is increased by treatment with PAMPs[ 4 , 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%